Study of Freedom of Speech and Expression in Legal Protection for Demonstrants in Indonesia - Sabela, Amira Rahma (Lex Scientia Law Review, 2017)
Freedom of speech and expression in the current era of democracy, moreover, this freedom is guaranteed by both national and international legal instruments, and is considered an important right in the life of the nation and society. The guarantee of freedom from intimidation and as a form of torture in any form, is also a guarantee of human rights as emphasized in the UN Human Rights Declaration and national laws and regulations. However, various cases of violence against demonstrators perpetrated by the government (state actors) have been in the spotlight of many parties. This paper tries to see how the study of freedom of speech and expression actually is from the point of view of human rights, in terms of various problems that limit it, be it social, cultural or religious values.